The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1084/jem.189.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MAGE-3 Epitopes Presented by HLA-DR Molecules to CD4+ T Lymphocytes

Abstract: MAGE-type genes are expressed by many tumors of different histological types and not by normal cells, except for male germline cells, which do not express major histocompatibility complex (MHC) molecules. Therefore, the antigens encoded by MAGE-type genes are strictly tumor specific and common to many tumors. We describe here the identification of the first MAGE-encoded epitopes presented by histocompatibility leukocyte antigen (HLA) class II molecules to CD4+ T lymphocytes. Monocyte-derived dendritic cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
138
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 48 publications
4
138
0
1
Order By: Relevance
“…In retrospect, we would have arrived at similar results had we initiated our search for T cell reactivity using ex vivo-sensitized human lymphocytes similar to that of investigators who have identified MHC class II-restricted epitopes for MAGE-3 (23,24). By using DR4-IE Tg mice, we circumvented the need to sensitize human lymphocytes to a large number of peptides, allowed for the naturally processed, immunodominant epitope to be presented in vivo, and established the basis for a workable tumor treatment model.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In retrospect, we would have arrived at similar results had we initiated our search for T cell reactivity using ex vivo-sensitized human lymphocytes similar to that of investigators who have identified MHC class II-restricted epitopes for MAGE-3 (23,24). By using DR4-IE Tg mice, we circumvented the need to sensitize human lymphocytes to a large number of peptides, allowed for the naturally processed, immunodominant epitope to be presented in vivo, and established the basis for a workable tumor treatment model.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, a need exists for the development of techniques useful in the identification of tumor-associated MHC class II-restricted epitopes in human cancers. While the targets of several CD4 ϩ T cells with potential anti-tumor activity have been identified (21)(22)(23)(24)(25)(26), no reliable, repeatable method for class II-restricted epitope identification has been established.…”
mentioning
confidence: 99%
“…These antigens are recognized by autologous cytotoxic T-lymphocytes (CTLs), which are restricted by human leukocyte antigen (HLA) class I molecules, and some antigenic peptides have been identified (Van den Eynde et al, 1997). Furthermore, these antigens are also reported to induce class II restricted T-cell responses (Chaux et al, 1999;Manici et al, 1999). Some of these antigens are expressed in various tumours of different histological origins, but not in normal tissues other than testis.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the remaining noncytotoxic CD4 þ clones released interferon-g on exposure to the melanoma line. Several other studies have reported isolation of HLA class II-restricted melanoma-specific CD4 þ CTLs, including clones recognising MAGE-3, NY-ESO1 and tyrosinase epitopes (Kobayashi et al, 1998;Chaux et al, 1999;Manici et al, 1999;Zarour et al, 2000). We isolated a CD4 þ HLA-DR11-restricted clone directed against an MAGE-3 epitope from one of our three normal donors.…”
Section: Discussionmentioning
confidence: 82%